State of Suffering : Political Violence and Community Survival in Fiji - Trnka, Susanna (Book collections on Project MUSE., 2008)
"How do ordinary people respond when their lives are irrevocably altered by terror and violence? Susanna Trnka was residing in an Indo-Fijian village in the year 2000 during the Fijian nationalist coup. The overthrow of the elected multiethnic party ..."--Publisher description